2018
DOI: 10.1002/ptr.6080
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharides exerts anti‐infective activity by inducing human cathelicidin antimicrobial peptide LL‐37 in respiratory epithelial cells

Abstract: Astragalus polysaccharides (APS), one of the major active components in Astragalus membranaceus, is an effective immunomodulator used in the treatment of immunological diseases in China. However, the anti-infective action and mechanism of APS is not fully known. In the present study, we found that APS induced the expression of human cathelicidin antimicrobial peptide LL-37, a key host anti-infective molecule, in both mRNA and protein levels in respiratory epithelial cells HBE16 and A549. Furthermore, the lysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…Traditionally, medicinal plants and foods have been generally used to treat various human diseases for thousands in China (Zhao, Tan, et al, ; Zhao, Wang, et al, ). Furthermore, medicinal plants and foods are also the main resource of bioactive compounds, including flavonoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, medicinal plants and foods have been generally used to treat various human diseases for thousands in China (Zhao, Tan, et al, ; Zhao, Wang, et al, ). Furthermore, medicinal plants and foods are also the main resource of bioactive compounds, including flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine plays an important role in the prevention and treatment of a variety of acute and chronic lung diseases, including chronic bronchitis (Liao, Hu, Chen, & Hung, ; Zhao, Tan, et al, ). Traditionally, sea buckthorn ( Hippophaë rhamnoides L.) fruit, a dual‐use resource of medicine and food, is used to treat cardiovascular diseases and lung disorders in traditional Chinese medicine and Tibetan medicine for a long history (Sayegh, Miglio, & Ray, ; Xu, Kaur, Dhillon, Tappia, & Dhalla, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, APS can inhibit the expression of inflammatory factors by inhibiting NF-κB signaling pathway [161] (Figure 5⑤). Thus, it was concluded that APS could effectively inhibit asthma by inhibiting ER stress and reduce the excessive secretion of respiratory mucus and respiratory inflammation in ovalbumin-induced severe asthma mice [162].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Administration of APS in experimental animals can promote the expression of cytokine interleukin-(IL-) 1β, tumor necrosis factor α (TNF-α), and interferon-γ (IFN-γ) genes and proteins [5,6], which can effectively activate and increase the number of macrophages [7] and stimulate the proliferation of peripheral blood T cells [8]. Recently, one study showed that APS can enhance immunity by inducing the production of the cathelicidin-derived antimicrobial peptide LL-37 in human respiratory epithelial cells through the activation of the pathways of p38 MAPK/JNK and NF-κ [9]. Studies have demonstrated that in vaccine immunization, APS has great potential as a potent adjuvant, enhancing the effect of antigen presentation by improving the performance of class II major histocompatibility complex molecules, which facilitates lymphocyte proliferation, increases the number of antibodies in serum, and increases the secretion of cytokine [10,11].…”
Section: Introductionmentioning
confidence: 99%